La ciencia en sí misma y la ciencia en nosotros: en torno al rol de la epistḗmē en el Fedro - García, Gabriel (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
The view of the τόπος ὑπερουράνιος in the Phaedrus is described according to three contents: justice (δικαιοσύνη), soundness (σωφροσύνη) and science (ἐπιστήμη). Only the latter is specified (247d6-e2). In „‘Der Geistcharakter des Überhimmlischen Raumes‘. Zur Korrektur der herrschenden Auffassung von Phaidros 247c-e”, W. Schwabe argued that this passage necessarily distinguishes the science “in what is” from the science “in what we now call beings”, and that the latter refers to science as a human practice of acquiring and transmitting knowledge. After reviewing his main arguments, I will examine this distinction in the whole dialogue, especially regarding the science “in what we now call beings”, in two moments: 1) the accurate description of the vision of science as memory, μνήμη, when the soul returns to the sensible realm, as well as its recovery in the erotic relation (both themes of the palinode) and 2) the relation between memory and science in the transmission of knowledge, in the critique of writing. The identification of science with the “immortal seed” contained in the dialectician’s speeches (276 e5-277 a4) will be linked to the analysis of procreation in beauty in the Symposion, showing that the ἐπιστήμη as content of the λόγοι expresses the dynamic relation between ideas. Therefore, the difference between “science in itself” and “science in us” must be conceived as a “structural feature” of the eidetic realm, in the same way as justice in the Republic (500c3-4) and, presumably, soundness.

La visión del τόπος ὑπερουράνιος en el Fedro se describe a partir de tres contenidos: la justicia (δικαιοσύνη), la sensatez (σωφροσύνη) y la ciencia (ἐπιστήμη). Solamente de esta última se brinda una mayor precisión (247d6-e2). En “‘Der Geistcharakter des Überhimmlischen Raumes’. Zur Korrektur der herrschenden Auffassung von Phaidros 247c-e”, W. Schwabe mostró que este pasaje distingue necesariamente la ciencia “en lo que es” de la ciencia “en lo que ahora denominamos seres”, y que esta última remite a la ciencia como práctica humana de adquisición y transmisión de conocimiento. Luego de revisar sus principales argumentos, examinaré esta distinción en el diálogo completo, especialmente respecto de la ciencia “en lo que ahora denominamos seres”, en dos momentos: 1) el resultado de la visión de la ciencia como memoria, μνήμη, cuando el alma regresa al ámbito sensible, así como su recuperación en la relación erótica (ambos temas de la palinodia) y 2) la forma como se relacionan memoria y ciencia en la transmisión del conocimiento, en la crítica de la escritura. La identificación de la ciencia con la “semilla inmortal” contenida en los discursos del dialéctico (276e5-277a4) se vinculará al análisis de la procreación en la belleza en el Banquete y se mostrará que la ἐπιστήμη, en tanto contenido de los λόγοι, expresa la relación dinámica entre las ideas. La diferencia entre la “ciencia en sí” y la “ciencia en nosotros” exige, por tanto, concebirla como un “rasgo estructural” del ámbito eidético, del mismo modo que la justicia en la República (500c3-4) y, cabe suponer, la sensatez.
Science in itself and science in us: on the role of the epistēmē in the Phaedrus
Keywords: Science; Memory; Soundness; Epistēmē; Phaedrus; Symposium; Republic; Ciencia; Memoria; Sensatez; Epistḗmē; Fedro; Banquete; República; https://purl.org/pe-repo/ocde/ford#6.03.01